2021
DOI: 10.1055/s-0041-1730413
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Speech-Recognition Performance in School-Aged Children with Cochlear Implants and Early Auditory-Verbal Intervention

Abstract: Background Considerable variability exists in the speech recognition abilities achieved by children with cochlear implants (CIs) due to varying demographic and performance variables including language abilities. Purpose This article examines the factors associated with speech recognition performance of school-aged children with CIs who were grouped by language ability. Research Design This is a single-center cross-sectional study with repeated measures for subjects across two language group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Along with other reports on the same pediatric population ( Deroche et al, 2023 ; Koirala et al, 2023 ; Wolfe et al, 2021 ), we explored motor cortex activity and its association with visual and auditory networks in children with CIs. We found an increase in HbO and a decrease in HbR in the motor cortex of all participants, irrespective of their hearing and language status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with other reports on the same pediatric population ( Deroche et al, 2023 ; Koirala et al, 2023 ; Wolfe et al, 2021 ), we explored motor cortex activity and its association with visual and auditory networks in children with CIs. We found an increase in HbO and a decrease in HbR in the motor cortex of all participants, irrespective of their hearing and language status.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five children between 7 and 18 years old were selected from patient records: 50 with CIs (CI group- Tables 1-A and 2-A ) and 25 controls with typical hearing and language development (TH group). Details about inclusion/exclusion criteria, participants’ demographic characteristics, hearing experience, and device use are provided in Wolfe et al (2021) , a study that reported exclusively on audiological outcomes. In the present study, CI recipients were divided into two groups based on their language skills: 26 children had age-appropriate language skills (referred to as Typical Language, or TL group) and 24 had language delays (referred to as Low Language, or LL group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children in the LL group were tted with a hearing aid and then implanted at a later age than children in group HL. This difference might seem small (on average, about 17 vs. 7 months for hearing aid tting, and 27 vs. 20 months for rst implantation), but at such young ages, we know that this has repercussions for the development of speech recognition skills (Ching et (Wolfe et al, 2021). Forty-ve children were bilaterally implanted, all 26 from the HL group and 19 in the LL group.…”
Section: General Methodsmentioning
confidence: 99%
“…Typically, multi-factorial models account for 50% of the variance (Sarant et al, 2001;Geers et al, 2003, and substantially less in adults e.g. Blamey et al, 2013;Lazard et al, 2012), using a combination of personal characteristics (cognitive skills, non-verbal intelligence, inherent language aptitudes), device parameters (electrode array, quality of mapping, and electric dynamic range), and communication mode (Geers et al, 2003;Dettman et al, 2013;Ambrose et al, 2015;Busch et al, 2019;Wolfe et al, 2021). We strongly suspect that the status of the auditory nerve and auditory brain (Feng et al, 2018;Sharma et al, 2002) would be additional factors to further explain why a given child derives much bene t from their device while another is not, despite both being implanted at a young age (Geers et al, 2016(Geers et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%